1990
DOI: 10.1111/j.1749-7345.1990.tb00947.x
|View full text |Cite
|
Sign up to set email alerts
|

Baker's Yeast as a Potential Substitute for Live Algae in Aquaculture Diets: Artemia as a Case Study

Abstract: In this study baker's yeast was evaluated as a substitute for live Dunuliella tertiolecta algae in the culture of the brine shrimp Artemia. Consumption of fresh baker's yeast resulted in poor growth and survival of brine shrimp. However, the nutritional value of the yeast sigaificantly improved after complete removal of the yeast cell wall by enzymatic treatment. Baker's yeast was also made digestible for Artemia by simple chemical treatment which did not reduce rigidity of the yeast cell. The external mannopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 27 publications
4
43
0
Order By: Relevance
“…This difference can be due to an improvement in yeast digestibility to Artemia caused by the mnn9 mutation. As postulated by Coutteau et al (11), the digestive tract of Artemia displays low mannase and high ␤-glucanase activities, complicating the digestion of yeast cells rich in cell wall-associated mannoproteins, such as WT yeast, and contributing to the proper digestion of yeast cells with reduced mannoprotein content, such as mnn9. As for the two microalga strains cultured in the same conditions, DT CCAP 19/6B always appeared to be a better feed for Artemia (Tables 4 and 5), even when bacteria were added.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This difference can be due to an improvement in yeast digestibility to Artemia caused by the mnn9 mutation. As postulated by Coutteau et al (11), the digestive tract of Artemia displays low mannase and high ␤-glucanase activities, complicating the digestion of yeast cells rich in cell wall-associated mannoproteins, such as WT yeast, and contributing to the proper digestion of yeast cells with reduced mannoprotein content, such as mnn9. As for the two microalga strains cultured in the same conditions, DT CCAP 19/6B always appeared to be a better feed for Artemia (Tables 4 and 5), even when bacteria were added.…”
Section: Discussionmentioning
confidence: 99%
“…This organism can be fed on a wide variety of feeds since it is a continuous nonselective and particle filter feeder (45). The most commonly used feed sources include live microalgae, such as Dunaliella tertiolecta (11,31), and baker's yeast (11), since they provide the basic nutrients for development of nauplii. Artemia is an excellent model organism to study the modes of action of probiotic and pathogenic bacteria, as it can easily be cultured under gnotobiotic conditions (29,30) and can be used as a vector for transferring probiotics to larvae of target species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that this was because yeast lacks certain essential nutrients, particularly ω3 HUFA's [29] or because it has a thicker cell wall and is more difficult to digest. Coutteau et al [52] found that yeast treated with sulfhydryl compounds improves its digestibility for Artemia. Further investigation on these lines may render yeast more useful for the maintenance of zooplankton.…”
Section: Discussionmentioning
confidence: 99%
“…Brewer's yeast has been recognized to have potential as well as a substitute for live food in the production of certain fish or as a potential replacement for fishmeal [88][89][90]. In addition, it has low content in phosphorous, meaning less water and environmental contamination than common fish meal and other plant-based alternate protein sources [91].…”
Section: Yeast Treats For Animalsmentioning
confidence: 99%